T.S. Eliot and the Malaise of Modernity: An Islamic critique - Md Mahmud Hasan Chowdhury (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
T.S. Eliot, a towering figure in the literary world, casts illuminating beams across the fragmented and spiritually barren modern landscape. This paper thoroughly examines Eliot’s oeuvre on modernity through an Islamic lens. By drawing upon Islam's philosophical and spiritual traditions, this research juxtaposes Eliot’s poetic evaluation and tapestry of Islamic perspectives as an ointment to heal the wounds of modern society. At the core of this inquiry, Islamic concepts such as the acknowledgment of the oneness of God (tawhid), mystical Islamic belief and practice (sufiism), and social solidarity (ummah) challenge Eliot’s perspective on modern sickness. This analysis also delves into Eliot’s poetic tapestry to explore how Eliot weaves a solution to the chaos of the modern era, including the fragmentation of identity, the decay of traditional values, and the existential crisis of humanity. This comparative discussion reveals how Islamic thought offers an alternative framework for comprehending the challenges of modernity. Ultimately, the research aims to contribute to a deeper understanding of Eliot’s enduring critiques and the multifaceted Islamic responses to the complexities and disorders of the modern man living under the influence of modern Western civilization.